Method for oxidative depolymerization of lignin by using transition metal-based metal organic framework
By preparing transition metal-based metal organic frame catalysts, the existing catalysts have been solved, and the existing catalysts have been efficiently oxidized and depolymerized lignin under mild conditions has been achieved, and the conversion rate and oil yield have been improved.
Patent Information
- Application Number
- CN202510119822.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-11
AI Technical Summary
The existing catalysts for oxidative and depolymerization of lignin have high cost, low catalytic activity and low metal utilization, making it difficult to efficiently oxidize and depolymerize lignin under mild conditions, resulting in low lignin conversion efficiency.
Using a transition metal-based metal organic frame catalyst, a catalyst such as Fe N@C with a positive dodecahedral structure was prepared by mixing the metal salt with 2-methylimidazole in solution, removing the solvent, and heating it with oxygen.
This catalyst can efficiently catalyze the oxidative and depolymerization of lignin under mild conditions, improve the conversion rate of lignin and the yield of lignin oil, and reduce the impact of metal on the environment.
Smart Images

Figure CN119793513A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass utilization and energy development, and particularly relates to a method for oxidatively depolymerizing lignin by utilizing a transition metal-based metal organic framework. Background Art
[0002] The disclosure of this background information is intended to enhance understanding of the general background of the invention and should not necessarily be regarded as an acknowledgment or any form of suggestion that this information constitutes the prior art already known to a person skilled in the art.
[0003] Lignin is the most abundant aromatic polymer in nature, composed of three phenylpropane units interconnected by ether and carbon-carbon bonds. It is considered an alternative source for the production of various polymers and biomaterials. However, the complex and diverse properties of lignin raw materials, including a three-dimensional, highly branched polymer structure and intricate CO / CC chemical bonds, have limited its further application. Lignin depolymerization methods are mainly divided into two categories: oxidative depolymerization and hydrodepolymerization. Oxidative depolymerization typically involves the use of oxidants to cleave the CC and CO bonds in lignin, producing phenols and other aromatic compounds. This method can be carried out under relatively mild conditions and effectively reduces the bond energy. It is particularly effective at cleaving CC bonds within the lignin structure, producing high-value chemicals such as aromatic aldehydes, acids, and ketones. Hydrodepolymerization, on the other hand, involves cleaving the chemical bonds in lignin through a catalytic hydrogenolysis process in the presence of hydrogen. This method can be carried out at lower temperatures and pressures, helping to preserve the aromatic structure of lignin while minimizing side reactions. The choice of catalyst is crucial in hydrodepolymerization. Common catalysts include compounds of precious metals such as palladium and non-precious metals such as nickel and copper.
[0004] Chinese patent CN 111760563 A discloses a lignin oxidative depolymerization catalyst, its preparation method, and its application. The catalyst is prepared by an impregnation method and is based on an inert support consisting of titanium dioxide, aluminum oxide, silicon dioxide, silicon carbide, activated carbon, or molecular sieves. It also contains one or more metal oxides, including tin, zirconium, copper, vanadium, nickel, iron, manganese, aluminum, and zinc, as active components. The catalyst efficiently catalyzes the oxidative depolymerization of lignin to produce aromatic compounds in an acetonitrile / water mixed solvent and molecular oxygen as the oxidant. Chinese patent CN 116410062 A discloses a method for catalyzing the oxidative depolymerization of lignin, comprising reacting a heterogeneous non-precious metal solid catalyst with a lignin substrate in an oxygen atmosphere. The catalytic oxidation selectively cleaves the internal bonds of the lignin under mild conditions to produce oxygenated aromatic compounds. However, the catalysts used in the oxidative depolymerization methods reported in existing literature are relatively expensive, have low catalytic activity, and exhibit low metal utilization.
[0005] The use of metal-organic frameworks (MOFs) as catalysts in the oxidative depolymerization of lignin has attracted considerable attention due to their cost-effectiveness and environmental friendliness. MOFs, with their unique pore structure and tunable chemical functionality, exhibit excellent performance in catalyzing the oxidative depolymerization of lignin, effectively catalyzing the cleavage of CC and CO bonds in lignin to produce high-value aromatic compounds.
[0006] Therefore, the current problem is the need to research and develop a catalyst with low cost, high metal utilization and high catalytic activity, which can efficiently oxidize and depolymerize lignin under mild conditions and improve the conversion efficiency of lignin. Summary of the Invention
[0007] In response to the problems of high cost, low catalytic activity and low metal utilization of current oxidative depolymerization catalysts for lignin, the present invention provides a transition metal-based metal-organic framework catalyst for oxidative depolymerization of lignin, which has a low metal loading and can effectively reduce the impact of metals on the environment.
[0008] Another object of the present invention is to provide a method for oxidative depolymerization of lignin using the above catalyst, wherein the oxidative depolymerization of lignin has mild conditions, excellent effects, high lignin conversion rate and high yield of lignin oil.
[0009] To achieve the above objectives, the present invention adopts the following technical solutions.
[0010] A method for preparing a transition metal-based metal-organic framework catalyst comprises the following steps: (1) Mixing a metal salt solution and a 2-methylimidazole solution and removing the solvent to obtain an intermediate; (2) Heating the intermediate at 800-1000°C in an oxygen-free environment for 1-4 hours; The metal salt is a mixture of any one of soluble manganese salt, iron salt, cobalt salt, copper salt and zinc salt.
[0011] The molar ratio of any one of the soluble manganese salt, iron salt, cobalt salt, copper salt and zinc salt is 1:(4-20).
[0012] The molar ratio of the zinc salt to 2-methylimidazole is 1:(2-10).
[0013] The solvents of the metal salt solution and the 2-methylimidazole solution are selected from at least one of methanol, ethanol and N,N-dimethylformamide.
[0014] Preferably, in step (1), the concentrations of the metal salt solution and the 2-methylimidazole solution are both 1%-10%; the mixing temperature of the metal salt solution and the 2-methylimidazole solution is 30°C-60°C; and the mixing time is 2h-24h.
[0015] Preferably, in step (2), the heating temperature is increased by 5°C / min-10°C / min.
[0016] A transition metal-based metal organic framework catalyst obtained by the above preparation method.
[0017] The catalyst has a regular dodecahedron shape and an average particle size of 100 nm to 800 nm. C is a carrier, and metal ions are coordinated with four N atoms.
[0018] The catalyst can catalyze the oxidative depolymerization of lignin, especially alkali-extracted lignin.
[0019] A method for oxidative depolymerization of lignin, comprising the following steps: (a) mixing lignin and the catalyst in an organic solvent and reacting them at high temperature and high pressure in the presence of oxygen; (b) separating the solid and liquid of the product after the reaction, washing the residue with an organic solvent, and combining the liquids to obtain the product liquid; (c) The solvent is removed from the product liquid to obtain lignin oil.
[0020] The lignin is alkali-extracted lignin. Preferably, the extraction step of the alkali-extracted lignin comprises: (i) adding a sodium hydroxide solution to agricultural and forestry waste, stirring at room temperature for reaction, and then filtering to obtain a filtrate; (ii) adjusting the pH of the filtrate to acidic and performing solid-liquid separation to obtain a precipitate; (iii) washing and drying the precipitate to obtain lignin.
[0021] The agricultural and forestry waste is selected from at least one of corn straw, wheat straw, pine, poplar, birch and giant fungus grass.
[0022] The solid-liquid ratio of the agricultural and forestry waste to the sodium hydroxide solution is 1 g: (5-20) mL, and the mass concentration of the sodium hydroxide solution is 1%-5%, preferably 2%-4%.
[0023] In step (i), the reaction temperature is 60° C.-100° C., preferably 70° C.-90° C. The reaction time is 1 h-5 h, preferably 2 h-4 h.
[0024] In step (a), the mass ratio of lignin to catalyst is (10-100):1. The organic solvent is selected from methanol, ethanol, acetone, γ-valerolactone, or dimethyl sulfoxide. The reaction temperature is 120°C-200°C. The reaction pressure is 0.1 MPa-0.5 MPa. The reaction time is 0.5-6 hours. Preferably, the reaction temperature is 180°C-200°C. The reaction pressure is 0.1 MPa-0.5 MPa. The reaction time is 2-6 hours.
[0025] The mechanism of the present invention is as follows: Taking FeN@C as an example, through Zn 2+ The coordination-unsaturated nitrogen atoms of ZIF-8 effectively capture the free Fe 3+ During the pyrolysis process, Zn 2+ ion nodes and Fe 3+ The Fe-ZIF-8 precursor is formed by the exchange of nodes. The Fe-ZIF-8 is thermally decomposed under high temperature and oxygen-free conditions, resulting in the vaporization of zinc nanoparticles to form FeN@C.
[0026] The present invention has the following advantages: This invention provides a transition metal-based catalyst for the oxidative depolymerization of lignin, prepared using MOF materials. Using ZIF-8 as a template, a dodecahedral transition metal-based nitrogen-doped carbon catalyst was prepared, which efficiently catalyzes the oxidative depolymerization of lignin. The method for the oxidative depolymerization of lignin provided by this invention, based on this catalyst, offers mild conditions, excellent results, and high lignin conversion and lignin oil yields. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the SEM image of FeN@C; Figure 2 is the efficiency of oxidative depolymerization of corn straw lignin by Fe N@C at different temperatures; Figure 3 is the efficiency of oxidative depolymerization of corn straw lignin by Fe N@C at different reaction times; Figure 4 is the efficiency of FeN@C in the oxidative depolymerization of lignin from different sources. DETAILED DESCRIPTION
[0028] A method for preparing a transition metal-based metal-organic framework catalyst comprises the following steps: (1) mixing and dissolving any one of a soluble manganese salt, an iron salt, a cobalt salt, or a copper salt with a zinc salt in a molar ratio of 1:(4-20) to obtain a metal salt solution with a concentration of 1%-10%; The metal salt solution and a 1%-10% 2-methylimidazole solution are mixed at a molar ratio of 1:2-1:5 at a temperature of 25°C-60°C for 2h-24h, and then the solvent is removed to obtain an intermediate; (2) The intermediate is heated to 800-1000°C at 5°C / min-10°C / min in an oxygen-free environment for 1-4 hours.
[0029] The heating temperature of the intermediate is mainly to vaporize zinc and leave the remaining metal particles to occupy the vacancies of ZIF-8, isolating oxygen to retain C, and maintaining it at 800℃-1000℃ for 1h-4h can achieve better yield.
[0030] The solvent will affect the formation and growth of MOF. In order to obtain a regular dodecahedral crystal form and a catalyst with better catalytic effect, the solvent in step (1) is selected from at least one of methanol, ethanol or N,N-dimethylformamide.
[0031] The present invention also provides a transition metal-based metal organic framework catalyst obtained by the above preparation method.
[0032] The catalyst has a regular dodecahedron morphology, C is a carrier, and manganese, iron, cobalt, copper and four N are coordinated. The catalyst has better catalytic efficiency when the average crystal particle size is 100nm-800nm.
[0033] The catalyst can catalyze the oxidative depolymerization of lignin, especially alkali-extracted lignin.
[0034] The present invention also provides a method for oxidative depolymerization of lignin, comprising the following steps: (a) mixing lignin and the catalyst in an organic solvent and reacting them at high temperature and high pressure in the presence of oxygen; (b) separating the solid and liquid of the product after the reaction, washing the residue with an organic solvent, and combining the liquids to obtain the product liquid; (c) The solvent is removed from the product liquid to obtain lignin oil.
[0035] The lignin is alkali-extracted lignin, which can be obtained by alkaline hydrolysis with sodium hydroxide according to a common method reported in the art. The source of the lignin is selected from at least one of corn straw, wheat straw, pine, poplar, birch and giant fungus grass.
[0036] Under optimized conditions, in step (a), the mass ratio of lignin to catalyst is (10-100):1; the organic solvent is selected from methanol, ethanol, acetone, γ-valerolactone, or dimethyl sulfoxide; the reaction temperature is 120°C-200°C; the reaction pressure is 0.1 MPa-0.5 MPa; and the reaction time is 0.5-6 hours. More preferably, the reaction temperature is 180°C-200°C; the reaction pressure is 0.1 MPa-0.5 MPa; and the reaction time is 2-6 hours.
[0037] The present invention will be further described below with reference to the embodiments and drawings, but the present invention is not limited to the following embodiments.
[0038] Example 1 Preparation of transition metal-based metal-organic framework catalysts Take 1.71g Zn(NO3)2·6H2O and 0.5g Fe(NO3)3·9H2O and dissolve them in 150mL methanol. Ultrasonicate to fully dissolve them to obtain solution A. 1.99g 2-methylimidazole is dissolved in 150mL methanol to obtain solution B. Add A to B and stir at 60℃ for 24h. Then wash with methanol several times and vacuum dry at 60℃. Then grind and crush, and in a tube furnace, use argon environment, heat to 900℃ at 5℃ / min and heat for 2h. After cooling to room temperature, grind into powder to obtain FeN@C catalyst, the SEM image of which is shown as follows: Figure 1 As shown: It presents a regular dodecahedral structure with an average particle size of 800nm, in which C is the carrier and Fe is coordinated with 4 N (FeN4).
[0039] According to the above method and molar ratio, Fe(NO3)3·6H2O was replaced by Co(NO3)2·6H2O, Cu(NO3)2·3H2O, Mn(NO3)2·4H2O and Ni(NO3)2·6H2O, respectively, to obtain Co N@C catalyst, Cu N@C catalyst, Mn N@C catalyst and Ni N@C catalyst.
[0040] Example 2 Oxidative Depolymerization of Alkali-Extracted Lignin Using Transition Metal-Based Metal-Organic Framework Catalysts 1. Preparation of Lignin Take 2 g of corn straw and add it to 50 mL of 5% sodium hydroxide solution. Stir at room temperature for 8 hours and filter. Adjust the pH of the filtrate to 2-3 with acid until a precipitate appears. Centrifuge again and wash several times with deionized water. Then dry at 80°C. The resulting lignin sample is labeled corn straw lignin.
[0041] 2. Oxidative depolymerization of corn straw lignin by different catalysts Take 0.1g corn straw lignin, 0.02g Fe N@C catalyst, and 10mL methanol and add them to the autoclave. Use molecular oxygen to purge 3-5 times and introduce oxygen to the pressure of 0.5MPa. React at 180℃ for 2h. After the reaction, filter and separate the filtrate and residue; rinse the residue with methanol and dry to obtain a solid residue. Mix the filtrate and the rinse liquid and concentrate under reduced pressure at 80℃ to obtain lignin oil. The same method is used to prepare Co N@C catalyst, Cu N@C catalyst, Mn N@C catalyst and Ni N@C catalyst in Example 1 for oxidative depolymerization of corn straw lignin to obtain lignin oil. The oxidative depolymerization effect is calculated according to the following formula: Lignin conversion rate = ×100%; Lignin oil yield = ×100%; Lignin residue yield = ×100%; Gas yield = 1 - lignin oil yield - lignin residue yield.
[0042] Table 1 Effects of different catalysts on oxidative depolymerization of corn straw lignin The results are shown in Table 1. The Fe N@C catalyst has the highest conversion rate and is more effective in breaking CC and CO bonds in lignin. In addition, Cu, Mn, and Co N@C also show good results in lignin conversion, while Ni N@C is less effective in lignin oxidative depolymerization, indicating that iron-based elements also exhibit different catalytic properties.
[0043] Example 3 Optimization of conditions for oxidative depolymerization of alkali-extracted lignin using transition metal-based metal-organic framework catalysts 1. Preparation of Lignin Take 2 g of corn straw and add it to 50 mL of 5% sodium hydroxide solution. Stir at room temperature for 8 hours and filter. Adjust the pH of the filtrate with acid until a precipitate appears. Centrifuge again and wash several times with deionized water. Then dry at 80°C. The resulting lignin sample is labeled corn straw lignin.
[0044] 2. Screening of depolymerization temperature 0.1 g corn straw lignin, 0.02 g FeN@C, and 10 mL methanol were added to an autoclave. Oxygen was introduced using molecular oxygen purges 3-5 times, and the pressure was brought to 0.5 MPa. The reaction was carried out at 120°C, 140°C, 160°C, 180°C, and 200°C for 2 h. After the reaction, the filtrate and residue were separated by filtration. The residue was rinsed with methanol, and the filtrate and rinse were combined and concentrated under reduced pressure at 80°C to obtain lignin oil. The residue was then dried at 80°C.
[0045] The results are as follows Figure 2 , in the temperature range of 120°C to 200°C, the changes in lignin residue yield, lignin oil yield, gas yield and lignin conversion rate. As the temperature increases, the lignin residue yield gradually decreases. This shows that high temperature helps to improve the conversion rate of lignin and reduce unreacted lignin residue. The yield of lignin oil increases with increasing temperature, especially between 160°C and 180°C. This shows that in this temperature range, lignin is more inclined to be converted into liquid products. Higher temperatures help to improve the conversion rate and oil yield of lignin, which may be because high temperatures provide enough energy to break the chemical bonds in lignin and promote the depolymerization reaction. From Figure 2As can be seen from the figure, 180°C is an ideal reaction temperature because at this temperature, the lignin conversion rate and oil yield both reach high levels, while the residue yield is low, indicating a relatively complete reaction. Further increasing the reaction temperature has a limited effect on the conversion rate. Although high temperatures can help improve conversion and oil yield, they also need to be controlled to avoid excessive gas production, which may indicate that some undesirable side reactions, such as excessive oxidation or pyrolysis, are occurring at high temperatures.
[0046] 3. Screening of Depolymerization Reaction Time 0.1 g corn straw lignin, 0.02 g FeN@C, and 10 mL methanol were added to an autoclave. Oxygen was introduced using molecular oxygen purges 3-5 times to a pressure of 0.5 MPa. The reaction was continued at 180°C for 0.5 h, 1 h, 2 h, 4 h, and 6 h, respectively. After the reaction, the filtrate and residue were separated by filtration. The residue was rinsed with methanol, and the filtrate and rinse were combined and concentrated under reduced pressure at 80°C to obtain lignin oil. The residue was then dried at 80°C.
[0047] Figure 3 The graph shows the changes in lignin residue yield, lignin oil yield, gas yield, and lignin conversion rate over reaction times of 0.5 to 6 hours. As can be seen, the lignin residue yield gradually decreases with increasing reaction time. This indicates that longer reaction times help improve lignin conversion and reduce unreacted lignin residue. The lignin oil yield increases with reaction time, with a particularly significant increase between 0.5 and 2 hours. This indicates that lignin is more likely to be converted into liquid products within this time range. The gas yield is low between 0.5 and 2 hours and increases with further reaction time, but remains relatively unchanged between 4 and 6 hours. This may mean that at longer reaction times, some lignin is converted into gaseous products, but after a certain time, the gas yield stabilizes. The lignin conversion rate increases with reaction time, indicating that longer reaction times facilitate lignin depolymerization. At 6 hours, the conversion rate approaches 90%, demonstrating the positive effect of longer reaction times on lignin depolymerization.
[0048] Example 4 Oxidative Depolymerization of Alkali-Extracted Lignin from Different Sources Using Transition Metal-Based Metal-Organic Framework Catalyst FeN@C 1. Preparation of Lignin Take 2g of pine shavings, add them to 50mL of 5% sodium hydroxide solution, stir at room temperature for 8h, and filter. Take the filtrate and adjust the pH to 2-3 with acid until a precipitate appears. Centrifuge again and wash with deionized water several times. Then dry at 80℃. The resulting lignin sample is labeled as pine lignin. The same method was used to obtain poplar lignin, wheat straw lignin, giant fungus grass lignin, and birch lignin using poplar powder, wheat straw, giant fungus grass lignin, and birch powder as raw materials, respectively.
[0049] 2. Oxidative depolymerization of corn straw lignin by different catalysts 0.1g of pine lignin, 0.02g of FeN@C catalyst, and 10mL of methanol were added to an autoclave. Oxygen was introduced using molecular oxygen purges 3-5 times to a pressure of 0.5 MPa. The reaction was carried out at 180°C for 2 hours. After the reaction, the filtrate and residue were separated by filtration. The residue was rinsed with methanol, and the filtrate and rinse were combined and concentrated under reduced pressure at 80°C to obtain lignin oil.
[0050] The same method was used to oxidatively depolymerize poplar lignin, wheat straw lignin, giant fungus lignin, and birch lignin to obtain lignin oil. The residue rate, oil yield, monomer yield, gas yield, and conversion rate were measured and calculated according to the method in Example 2.
[0051] Figure 4 The residue yield, oil yield, gas yield, and lignin conversion rate of wheat straw lignin, giant grass lignin, poplar lignin, pine lignin, and birch lignin are shown. Wheat straw lignin had the lowest residue yield, while birch lignin had the highest. This indicates that the conversion efficiency of lignins from different sources varies during the depolymerization process. Regarding lignin oil yield, wheat straw lignin had the highest oil yield, while birch lignin had the lowest oil yield. Wheat straw lignin had the highest conversion rate, while pine lignin had the lowest conversion rate. Lignins from different sources behave differently during oxidative depolymerization due to differences in their chemical composition and structure. Wheat straw lignin, as an herbaceous plant, contains the three key lignin monomers H, G, and S, while lignins from softwood and hardwood biomasses such as pine and birch may lack one or two of these key monomers. This leads to significant structural differences in the lignins, ultimately resulting in low lignin oil yields and low lignin conversion rates.
[0052] Example 5 Preparation of transition metal-based metal-organic framework catalysts (1) Dissolve 2.97 g, 4.46 g, and 5.94 g of Zn(NO3)2·6H2O and 0.5 g of Fe(NO3)3·9H2O in 150 mL of methanol, and sonicate to obtain metal salt solutions with different ratios of zinc salt to iron salt. (2) Dissolve 1.99 g of 2-methylimidazole in 150 mL of methanol to obtain a 2-methylimidazole solution; (3) The metal salt solution and 2-methylimidazole solution were mixed respectively and stirred at room temperature for 24 h. The insoluble matter was then washed with methanol several times, dried under vacuum at 60 °C, and ground to obtain an intermediate. (4) The intermediate was placed in a tube furnace and heated at 900 °C for 2 h at a rate of 5 °C / min under an argon atmosphere. After cooling to room temperature, it was ground into powder, and a regular dodecahedral Fe N@C catalyst was obtained. As the molar ratio of zinc salt to 2-methylimidazole gradually decreased, the average particle size of the crystals gradually increased.
[0053] Example 6 Preparation of transition metal-based metal-organic framework catalysts (1) Dissolve 1.71 g of Zn(NO3)2·6H2O and 0.5 g of Fe(NO3)2·9H2O in 150 mL of methanol and sonicate to obtain a metal salt solution. (2) Dissolve 2.788 g of 2-methylimidazole in 150 mL of methanol to obtain a 2-methylimidazole solution; (3) The metal salt solution and 2-methylimidazole solution were mixed and stirred at room temperature for 24 h, and then the insoluble matter was washed with methanol several times, dried under vacuum at 60 °C, and then ground to obtain an intermediate; (4) The intermediate was placed in a tube furnace and heated at 900°C for 2 h at a rate of 5°C / min under an argon atmosphere. After cooling to room temperature, the intermediate was ground into powder to obtain a dodecahedral FeN@C catalyst. Compared with Example 1, the molar ratio of zinc salt to 2-methylimidazole increased, and the average particle size of the crystals gradually decreased.
[0054] Example 7 Preparation of transition metal-based metal-organic framework catalysts (1) Dissolve 1.71 g Zn(NO3)2·6H2O and 0.5 g Fe(NO3)2·9H2O in 150 mL ethanol, DMF, or water and sonicate to obtain a metal salt solution. (2) Dissolve 1.99 g of 2-methylimidazole in 150 mL of ethanol, DMF, or water to obtain a 2-methylimidazole solution; (3) The metal salt solution and 2-methylimidazole solution were mixed and stirred at room temperature for 24 h, and then the insoluble matter was washed with ethanol several times, dried under vacuum at 60 °C, and then ground to obtain an intermediate; (4) The intermediate was placed in a tube furnace and heated at 900 °C for 2 h at 5 °C / min under an argon atmosphere; after cooling to room temperature, it was ground into powder.
[0055] In ethanol and DMF, the catalyst still forms dodecahedral particles, while in water, it forms flake-like particles. Changing the solvent will affect the catalyst's morphology, and thus the catalytic effect.
[0056] Example 8 Preparation of transition metal-based metal-organic framework catalyst (1) Dissolve 1.71 g of Zn(NO3)2·6H2O and 0.5 g of Fe(NO3)2·9H2O in 150 mL of methanol and sonicate to obtain a metal salt solution. (2) Dissolve 1.99 g of 2-methylimidazole in 150 mL of methanol to obtain a 2-methylimidazole solution; (3) The metal salt solution and 2-methylimidazole solution were mixed and stirred at 30°C, 40°C, and 50°C for 24 h, and then the insoluble matter was washed with methanol several times, vacuum dried at 60°C, and then ground to obtain an intermediate; (4) The intermediate was placed in a tube furnace and heated at 900°C for 2 h at a rate of 5°C / min under an argon atmosphere. After cooling to room temperature, the intermediate was ground into powder. A dodecahedral FeN@C catalyst was obtained. Measurement of the average particle size revealed that the average particle size of the crystals gradually increased with increasing mixing temperature in step (3).
[0057] The foregoing is merely an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application should all be included within the scope of the claims of the present application.
Claims
1. A method for preparing a transition metal-based metal organic framework catalyst, characterized in that: The following steps are involved: (1) mixing a metal salt solution and a 2-methylimidazole solution and removing the solvent to obtain an intermediate; (2) heating the intermediate at 800°C-1000°C in an oxygen-free environment for 1-4 hours; The metal salt is a mixture of any one of soluble manganese salt, iron salt, cobalt salt and copper salt and zinc salt.
2. The preparation method according to claim 1, characterized in that: The molar ratio of any one of the soluble manganese salt, iron salt, cobalt salt, copper salt and zinc salt is 1:(4-20); The molar ratio of the zinc salt to 2-methylimidazole is 1:(2-10); The solvents of the metal salt solution and the 2-methylimidazole solution are selected from at least one of methanol, ethanol and N,N-dimethylformamide.
3. The preparation method according to claim 1, characterized in that: In step (1), the concentrations of the metal salt solution and the 2-methylimidazole solution are both 1%-10%; the mixing temperature of the metal salt solution and the 2-methylimidazole solution is 30°C-60°C; and the mixing time is 2h-24h; In step (2), the heating temperature is increased by 5°C / min-10°C / min.
4. A transition metal-based metal organic framework catalyst obtained according to the preparation method according to any one of claims 1 to 3, characterized in that: The catalyst has a regular dodecahedron shape and an average particle size of 100nm-800nm; C is a carrier, and metal ions are coordinated with four Ns.
5. Use of the transition metal-based metal organic framework catalyst as claimed in claim 4 in catalyzing the oxidative depolymerization of lignin.
6. A method for oxidative depolymerization of lignin, characterized in that: The following steps are involved: (a) mixing lignin and the transition metal-based metal organic framework catalyst as claimed in claim 4 in an organic solvent and reacting them at high temperature and high pressure in the presence of oxygen; (b) separating the solid and liquid of the product after the reaction, washing the residue with an organic solvent, and combining the liquid to obtain the product liquid; (c) The solvent is removed from the product liquid to obtain lignin oil.
7. The method according to claim 6, characterized in that The lignin is alkali-extracted lignin; the extraction steps of the alkali-extracted lignin include: (i) adding a sodium hydroxide solution to agricultural and forestry waste, stirring at room temperature for reaction, and then filtering to obtain a filtrate; (ii) adjusting the pH of the filtrate to acidic and performing solid-liquid separation to obtain a precipitate; (iii) washing and drying the precipitate to obtain lignin.
8. The method according to claim 7, characterized in that The agricultural and forestry waste is selected from at least one of corn straw, wheat straw, pine, poplar, birch and giant fungus grass; The solid-liquid ratio of the agricultural and forestry waste to the sodium hydroxide solution is 1g: (5-20)mL, and the mass concentration of the sodium hydroxide solution is 1%-5%, preferably 2%-4%; In step (i), the reaction temperature is 60° C.-100° C., preferably 70° C.-90° C. The reaction time is 1 h-5 h, preferably 2 h-4 h.
9. The method according to claim 6, characterized in that In step (a), the mass ratio of lignin to catalyst is (10-100):1; The organic solvent is selected from methanol, ethanol, acetone, γ-valerolactone or dimethyl sulfoxide; The reaction temperature is 120°C-200°C; the reaction pressure is 0.1MPa-0.5MPa; and the reaction time is 0.5h-6h.
10. The method according to claim 6, characterized in that The reaction temperature is 180°C-200°C; the reaction pressure is 0.1MPa-0.5MPa; and the reaction time is 2h-6h.
Citation Information
Patent Citations
Lignin oxidative depolymerization catalyst as well as preparation method and application thereof
CN111760563A
Method for catalyzing oxidative depolymerization of lignin
CN116410062A